THE IMPACT OF INTEGRATION BETWEEN ACCOUNTING DISCLOSURE AND COMMERCIAL IDENTITY ON THE SUSTAINABILITY OF COMPETITIVE ADVANTAGE - Jasim Gshayyish Zwaid (ZILLZELL MEDIA PRIMA, 2025)
In the highly competitive business world, insurance companies need strategic tools to strengthen their market position. This study aims to comprehend how integrating brand identity and accounting disclosure affects preserving competitive advantage through a field study of a sample of public and private insurance companies in Iraq. The study employed quantitative measures such as advertising expenditures, investment income, business profits, and insurance portfolio performance. The results showed that companies like Gulf and Al Hamra were able to outperform their rivals and hold onto their revenue and profits by skillfully combining financial disclosure with a distinctive brand identity. It also demonstrated that open disclosure increases investor and customer confidence, even though brand identity is crucial for establishing a company's reputation and encouraging loyalty. The study concluded that, especially in a sensitive industry like insurance, integrating the financial and marketing aspects is a competitive necessity rather than an institutional luxury. The study recommended using a dual disclosure model that combines accounting transparency with brand communication messaging to ensure greater trust and long-term superiority. The study also filled a scientific gap in the Arabic literature by providing an analytical framework for evaluating long-term competitive performance. In the context of insurance, the interdependent relationship between financial disclosure and brand identity was rarely discussed in Arabic literature.